Development of a quality check station in a pharmaceutical industry to achieve zero defect production using PDCA cycle - Mahmud, Khairus Syakirah; Nasry, Nasrul Ashraf; Hilmy, Irfan; Ismail, Md Yusof (Asian Research Publishing Network (ARPN), 2015)
This paper reports the result of a research in a pharmaceutical industry in Malaysia. The data have been collected and analyzed because of the some issues occurred in company X. There is need of adding a check station in the company. Moreover, the issues on the health of human eyes sight that required to be considered during quality check. In order to avoid the rejection of capsule, the quality check station is developed. The inspection table and the standard light intensity on the inspection table must be taken into account for better capsule production result. This also directly affects the health of human eyes and should be considered. The objective of this research is to enhance the production and avoid the rejection parts. There is one strategy for the continuously improvement. The lean manufacturing approach has been carried out in problem solving using the PDCA technique. The finding reveals that application of lean manufacturing using PDCA helps in solving the problem in the process. Thus, the inspection table has two sides of lights. The inspection table has to be equipped with a reflector in order to achieve the standard light intensity for human eyes. Consequently, this will reduce rejection of parts and aids in faster inspection.